Non-fasting High-Density Lipoprotein Is Associated With White Matter Microstructure in Healthy Older Adults - Johnson, Nathan F.; Gold, Brian T.; Ross, Dorothy; Bailey, Alison L.; Clasey, Jody L.; Gupta, Vedant; Leung, Steve W.; Powell, David K. (Frontiers in Aging Neuroscience, 2019)
A growing body of evidence indicates that biomarkers of cardiovascular risk may be related to cerebral health. However, little is known about the role non-fasting lipoprotein play in assessing age-related declines in a cerebral biomarker sensitive to vascular compromise, white matter (WM) microstructure. High-density lipoprotein cholesterol (HDL-C) is atheroprotective and low-density lipoprotein cholesterol (LDL-C) is a major atherogenic lipoprotein. This study explored the relationships between non-fasting levels of cholesterol and WM microstructure in healthy older adults. A voxelwise and region of interest approach was used to determine the relationship between cholesterol and fractional anisotropy (FA). Participants were 87 older adults between the ages of 59 and 77 (mean age = 65.5 years, SD = 3.9). Results indicated that higher HDL-C was associated with higher FA in diffuse regions of the brain when controlling for age, sex, and body mass index. HDL-C was also positively associated with FA in the corpus callosum and fornix. No relationship was observed between LDL-C and FA. Findings suggest that a modifiable lifestyle variable associated with cardiovascular health may help to preserve cerebral WM.